Strike Up the Band Derek Deane dances with the Gershwins, Peter Schaufuss evokes a trio of celebrity icons review - Hutera, Donald (Dance Books Ltd., Alton,Hampshire (UK), 2008)
Review of Derek Deane dances with the Gershwins, Peter Schaufuss evokes a trio of celebrity icons. A motley collection of Marceau-like mimes, nannies, nuns and can-can girls.